The Effect of Relevance on Children's Multiple Text Reading: Evidence From Eye Movements - Häikiö, Tuomo; Kanerva, Oksana; Erdmann, Norbert; Mikkilä‐Erdmann, Mirjamaija; Kaakinen, Johanna K. (Wiley, 2026)
We examined how Finnish children read and integrate information across multiple expository texts when given an inquiry task. We were interested in how task-relevance of text information affects readers' eye movements and whether the eye movements are connected to the quality of an essay written after reading. We were also interested in differentiating between the effects of technical reading skill and reading comprehension in respect to these processes. In total, 24 5th and 6th grade Finnish native-speakers completed the experiment. Prior to testing, the participants were told that at the end of the testing session, they would have to complete an inquiry task (e.g., “What's the difference between human and dog hearing?”). During an eye tracking experiment, the participants read two science texts on the topic of the inquiry task. The texts contained both task-relevant and task-irrelevant text segments. After the reading task, the children wrote an essay to complete the inquiry task. Furthermore, participants' technical reading skill and reading comprehension were measured with an independent classroom test. It was shown that the task-relevant segments were read longer than the task-irrelevant segments during first-pass reading. Moreover, reading skills modulated the effect of relevance, as weaker comprehenders were less likely to regress within an irrelevant segment. Furthermore, the relevance effect was more pronounced for the better technical readers with respect to look-backs. No reliable effects were found for the essay-writing task. The results imply that the participants were able to detect which parts of the text were relevant and adjusted their reading accordingly, based on their reading skills. However, they did not seem to form a coherent memory representation of the relevant text contents in order to perform well in the essay writing task.